2011
DOI: 10.1093/gerona/glr189
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Cognitive Decline Among the Oldest Old in Okinawa: In Search of a Mechanism. The KOCOA Project

Abstract: The study aim was to test whether the metabolic syndrome or its components predicted cognitive decline among persons aged 80 years and older (mean 85.0 years). Participants were members of the "Keys to Optimal Cognitive Aging Project," a prospective cohort study in Okinawa, Japan. Metabolic syndrome was assessed at baseline. Cognitive functions were assessed annually for up to 3 years. One hundred and forty-eight participants completed at least one follow-up with 101 participating in all three assessments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 72 publications
2
54
0
Order By: Relevance
“…A detailed description of the recruitment process has been described elsewhere [26,27]. Briefly, researchers visited 21 senior centers, explained the study protocol, and asked them to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the recruitment process has been described elsewhere [26,27]. Briefly, researchers visited 21 senior centers, explained the study protocol, and asked them to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…It is a simple scoring system with no single dominant component, and is used by several studies evaluating the association of MetS with human cognition [13,26,36]. In the present study, we evaluated the association of MetS as a whole as well as the individual risk components with the different parameters of cognition.…”
Section: Age Groupsmentioning
confidence: 99%
“…Life expectancy is on the rise and the oldest old (≄80 years old) [1, 2] is the fastest growing demographic in the world [3]. Several studies have demonstrated that high cardiovascular risk at midlife, particularly hypertension (HTN), is linked to subsequent increased risk of dementia [4–8].…”
Section: Introductionmentioning
confidence: 99%